Potential of MR spectroscopy for assessment of glioma grading - Bulik, Martin; Jancalek, Radim; Vanicek, Jiri; Skoch, Antonin; Mechl, Marek (Clinical neurology and neurosurgery, 2013)
BACKGROUND: Magnetic resonance spectroscopy (MRS) is an imaging diagnostic method based that allows non-invasive measurement of metabolites in tissues. There are a number of metabolites that can be identified by standard brain proton MRS but only a few of them has a clinical significance in diagnosis of gliomas including N-acetylaspartate, choline, creatine, myo-inositol, lactate, and lipids. METHODS: In this review, we describe potential of MRS for grading of gliomas. RESULTS: Low-grade gliomas are generally characterized by a relatively high concentration of N-acetylaspartate, low level of choline and absence of lactate and lipids. The increase in creatine concentration indicates low-grade gliomas with earlier progression and malignant transformation. Progression in grade of a glioma is reflected in the progressive decrease in the N-acetylaspartate and myo-inositol levels on the one hand and elevation in choline level up to grade III on the other. Malignant transformation of the glial tumors is also accompanied by the presence of lactate and lipids in MR spectra of grade III but mainly grade IV gliomas. It follows that MRS is a helpful method for detection of glioma regions with aggressive growth or upgrading due to favorable correlation of the choline and N-acetylaspartate levels with histopathological proliferation index Ki-67. Thus, magnetic resonance spectroscopy is also a suitable method for the targeting of brain biopsies. CONCLUSIONS: Gliomas of each grade have some specific MRS features that can be used for improvement of the diagnostic value of conventional magnetic resonance imaging in non-invasive assessment of glioma grade.
Keywords: Humans; Glioma; metabolismus lipidů; gliom; Lipid Metabolism; lidé; kyselina asparagová; Lactates; Aspartic Acid; Brain Neoplasms; laktáty; Choline; Neurosurgical Procedures; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; nádory mozku; Creatine; neurochirurgické výkony; inositol; kreatin; cholin; Inositol